Willingness to invest in one's own health depending on profession and education in the South Bohemian Region - Veselá, Romana; Kandilaki, Daniela, 1985-; Tripes, Stanislav; Vysoká škola ekonomická v Praze. Fakulta managementu (2024)
The thesis focuses on the willingness of residents of the South Bohemian Region to invest in their health, taking into account their monthly income, employment and level of education. The main goal is to determine how income, profession and education influence this willingness. The research was conducted through a questionnaire survey and the data obtained from 210 respondents were analyzed using statistical methods, such as ordinal and binary logistic regression and chi-square test of independence. The statistical software IBM SPSS Statistica was used to process statistical data, which is the most suitable in terms of software accessibility and the nature of the data. The knowledge obtained can provide valuable information for improving preventive measures and health promotion in this area. The results of the work can thus be the basis for further detailed research or just informative for policymakers.
Vedoucí práce: Daniela Kandilaki
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses